Neurological symptoms and complications of influenza in the elderly - Šín, Robin; Kubiska, Miroslav (Neuro endocrinology letters, 2024)
BACKGROUND: An in-depth study of neurological symptoms and complications of influenza in elderly patients. This population group is more susceptible to complications of the disease and these complications are more likely to end in death. METHODS: A retrospective analysis of patient data was performed. All patients aged 65 years and older were included in the study. The study period was from the 1st of January , 2018 to 31st of December, 2021. All symptoms and complications of influenza were analyzed. Especially neurological and general symptoms were analyzed. Data were extracted from the complete medical records of the patients. RESULTS: The most common symptoms of influenza in the elderly were fever in 218 cases (83.52%), cough in 189 patients (72.41%), general weakness in 182 (69.73%) and fatigue in 166 patients (63.6%). Myalgias were experienced by 106 patients (40.61%) and arthralgias by 101 patients (38.7%). Headache occurred in only 21 patients (8.06%). Encephalopathy was observed in 7 elderly patients (2.68%) during hospitalization. Influenza encephalitis was noted in 2 cases. CONCLUSION: The most common neurological symptoms of influenza in more than half of the elderly are general weakness and increased fatigue. Myalgias are common, headache less often. Nausea is not uncommon. Of the complications, encephalopathy is the most common. Cases of influenza encephalitis have also been reported. We have not encountered a stroke. Concerning other complications, bacterial pneumonia was the most common.
Keywords: Humans; Influenza, Human; Nervous System Diseases; Muscle Weakness; Female; Aged; myalgie; senioři; lidé; bolesti hlavy; Fever; Fatigue; svalová slabost; Headache; horečka; chřipka lidská; Myalgia; ženské pohlaví; Male; Retrospective Studies; nemoci nervového systému; Cough; Aged, 80 and over; únava; senioři nad 80 let; retrospektivní studie; kašel; mužské pohlaví